Down‐regulated in OA cartilage, SFMBT2 contributes to NF‐κB‐mediated ECM degradation. Issue 11 (22nd August 2018) - Hussain, Safdar; Sun, Mengyao; Min, Zixin; Guo, Yuanxu; Xu, Jing; Mushtaq, Nosheen; Heng, Lisong; Huang, Huang; Zhao, Yitong; Yuan, Ying; Hussain, Nazim; Zhang, Fujun; et al.
Abstract: The interplay between anabolic and catabolic factors regulates cartilage matrix homoeostasis. In OA, this balance is disrupted which results in cartilage degradation involving a plethora of inflammatory factors. Here, we identify a novel gene "Scm‐like with four MBT domains protein 2" (SFMBT2) negatively regulated in OA cartilage. Articular cartilage from human OA patients undergoing knee arthroplasty surgery exhibited significantly decreased levels of SFMBT2 compared to the normal controls. Down‐regulation of SFMBT2 by specific siRNA disturbed the metabolic homoeostasis and led to decreased expression of anabolic genes (SOX9, COL2A1) while increasing the expression of catabolic genes (MMP13 and ADAMTS4), in human chondrocytes. Finally, we revealed that SFMBT2 intervention by siRNA contributed to the catabolic phenotype of human chondrocytes mediated by NF‐kB pathway.